# Algebra

Solve by using the quadratic formula
x^2=-7x+12

First, put all the terms on one side.

x^2=-7x+12

x^2 + 7x -12 = 0

If the original sign for the 12 were negative, this would lead you to:

x^2 + 7x + 12 = 0

This could factor into:

(x+3)(x+4) = 0

However, as you have formula posted, it cannot be factored.

I hope this helps. Thanks for asking.

x=(-7/2)+(sq97)/(2),(-7/2)-(sq97)/(2)

1. 👍
2. 👎
3. 👁

## Similar Questions

1. ### algebra

Unit 4: Quadratic Functions and Equations Lesson 6: The Quadratic Formula and the Discriminant 1.) a=5, b=9, c=-4 2.) C 3.) No solution 4.) x=-2, x=1.25 5.) x=-9, x=3 6.) quadratic formula 7.) 2 8.) 11cm by 16cm

2. ### math help how do i do this

Decide which part of the quadratic formula tells you whether the quadratic equation can be solved by factoring. −b b^2 − 4ac 2a Use the part of the quadratic formula that you chose above and find its value, given the following

3. ### math

Heather is solving an equation by graphing the expressions on both sides. If her graph intersects at an infinite number of points, which statement could describe the equation Heather is attempting to solve? A. One side of the

4. ### algebra1

what formula should i use to solve this quadratic formula? 2x2 + 4x + 2 = 0.

1. ### math

Jimmy began deriving the quadratic formula as shown. ax² +bx +c = 0 x² +b/ax+c/a=0 x² +b/ax=−c/a x² +b/ax+(b/2a)² =−c/a+(b/2a)² What should Jimmy do next? Subtract x² from each side. Factor the trinomial. Add x² to

2. ### algebra

Solve this quadratic equation using the quadratic formula. x^2 + 8x - 5 = 0

3. ### Math

a) Explain the relationship between the axis of symmetry and the quadratic formula. b) We know that the quadratic formula can be used to determine the roots of a quadratic function. However, the quadratic formula also reveals how

4. ### i need help..algebra/math

solve by using the quadratic formula: x2 plus x minus 2 equal 0 I know the formula is a=1 b=1 c=2 I'm having trouble solving...please help.

1. ### College Algebra

I could not figure out the answer to this Problem: The quadratic function f(x)= -2x^2 =4x +3 can be used to solve the following inequality: -2x^2 -4x < -3 First use the Quadratic Formula to find the x-intercept of f. This problem